FEATURES SOCIAL ADAPTATION IN GLOBALIZATION’S CONDITIONS - Кармадонова, Т. М. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article reveals the crucial importance of social adaptation in the context of globalization.